Can competition spoil reciprocity? A laboratory experiment - Stefan Bauernschuster; Oliver Falck; Niels Daniel Große (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates how group membership and competition among trustors interact with trust and trustworthiness in a laboratory one-shot trust game. To analyze these effects, we apply a 2x2 design. We induce group membership by letting subjects play coordination games with clear focal points, leading to higher investments and trustworthiness. Introducing competition leads to a decrease in trustworthiness, especially among partners. We argue that once competition comes into play, trustees perceive trustors' investments as the outcomes of a competitive bidding process rather than good intentions, which reduces reciprocity.
Keywords: C92; G11; Z13; L14; 330; trust; reciprocity; investment game; group membership; competition; Gruppenarbeit; Vertrauen; Wettbewerb; Austauschtheorie; Spieltheorie; Test